Effect of Vitamin D Supplementation on Some Inflammatory Biomarkers in Type 2 Diabetes Mellitus Subjects: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Yu, Yanting; Tian, Liqiang; Xiao, Yanyu; Huang, Guowei; Zhang, Meilin (Annals of nutrition and metabolism, 2018)
The mechanism, by which vitamin D influences inflammatory biomarkers in type 2 diabetes mellitus (T2DM), is not very well known. Thus, a meta-analysis of randomized controlled trials was conducted to assess the effect of vitamin D supplementation on some inflammatory biomarkers in T2DM subjects. We searched randomized controlled trials from PubMed and the Cochrane Library in October 2017 and conducted a meta-analysis to evaluate the effectiveness of vitamin D supplementation on high-sensitivity C-reactive protein (hs-CRP), tumor necrosis factor-alpha (TNF-α) and interleukin-6 (IL-6). Either a fixed-effects or a random-effects model was used to calculate pooled effects. We identified 13 studies that met our inclusion criteria. The results indicated that the vitamin D supplementation significant decreased the hs-CRP level by 0.45 μg/mL, whereas the vitamin D supplementation did not  influence the TNF-α and IL-6. Subgroup analysis showed that vitamin D significantly lowered hs-CRP by 0.34 μg/mL among trials with a daily vitamin D dose ≤4,000 IU and by 0.31 μg/mL among trials with time of vitamin D supplementation > 12 weeks. Vitamin D supplementation is beneficial for the reduction of hs-CRP inT2DM subjects but does not have a significant influence on TNF-α and IL-6 in T2DM subjects.